Long acting ophthalmic formulation of indomethacin: Evaluation of alginate gel systems - Pandit J.K.; Bharathi D.; Srinatha A.; Ridhurkar D.N.; Singh S. (My University, 2025)
Different types of in situ gelling systems of indomethacin, in sodium alginate vehicle, were prepared and evaluated for their pharmaceutical properties including viscosity, sterility and drug content uniformity. The gelling efficacy of the prepared systems was evaluated by using an in house fabricated gelation cell. The in vitro release kinetics of the prepared systems was determined in simulated tear. The gelling time and the nature of the gel formed were dependent on the concentration of sodium alginate present in the systems. The drug release from these systems was extended up to 8 h and predominately followed zero-order kinetics.